2011
DOI: 10.1309/ajcpwabwfbu9eyxr
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Curriculum for Laboratory Management Training for Pathology Residents

Abstract: Through the combined efforts of the American Pathology Foundation (APF), the American Society for Clinical Pathology (ASCP), and the Program Directors Section (PRODS) of the Association of Pathology Chairs (APC), a needs assessment was performed via a survey on the PRODS listserv, workshops at the APC/PRODS annual meetings in 2009 and 2010, and a Work Group of representatives of APF, ASCP, and PRODS. Residency program needs and resource constraints common to training pathology residents in practice and laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…[22] Another wiki that attempts to define a pathology curriculum is the American Society for Clinical Pathology's consensus curriculum for laboratory management training (http://wiki.ascp.org/wikka.php?wakka=Curriculum); this wiki is much like the Massachusetts General Hospital Pathology Informatics Wiki in that it culls and links usable content from sources like Wikipedia and cdc.gov. [26] All of these approaches are valid and are likely to provide useful sources of publically available pathology informatics didactic material.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[22] Another wiki that attempts to define a pathology curriculum is the American Society for Clinical Pathology's consensus curriculum for laboratory management training (http://wiki.ascp.org/wikka.php?wakka=Curriculum); this wiki is much like the Massachusetts General Hospital Pathology Informatics Wiki in that it culls and links usable content from sources like Wikipedia and cdc.gov. [26] All of these approaches are valid and are likely to provide useful sources of publically available pathology informatics didactic material.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Key indications of expert interpretation of medical images are consistent, accurate and efficient diagnostic performance, which require not only dedicated training and experience but some degree of talent, aptitude and motivation. Experts are better able to search, process, and interpret larger perceptual units than those with less skill because they are better able to recognize these units more efficiently and effectively as configurations or chunks of information rather than individual pieces [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The mechanism behind this phenomenon is thought to be due to perceptual and/or cognitive tuning to the visual task as the observer encounters more exemplars over time with suitable training and feedback.…”
Section: Navigating Through Imagesmentioning
confidence: 99%
“…7 Briefly, that survey found that 48% of pathology training programs devoted more than 20 hours to practice and laboratory management topics. was part of a work group of the American Pathology Foundation (APF), the American Society for Clinical Pathology (ASCP), and the Program Directors Section that developed and distributed a survey on management training practices to the Program Directors Section listserv.…”
Section: Problemmentioning
confidence: 99%